2013
DOI: 10.1155/2013/581856
|View full text |Cite
|
Sign up to set email alerts
|

Mantle Cell Lymphoma and Involvement of the Orbit and Ocular Adnexa

Abstract: Orbital and ocular adnexal lymphomas are rare and represent around 1-2% of lymphomas and about 8% of the extranodal lymphomas. However, these entities represent the majority of orbital malignancies. Lymphomas of the ocular adnexal region are primary or secondary lymphomas, and the majority of them are composed of small, mature lymphocytes, which provide a large differential diagnosis. Thus, these entities are not easily distinguished from indolent lymphoid processes such as reactive lymphoid hyperplasia. Extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…The blastoid and pleomorphic variants behave more aggressively than other MCL variants. 8 Median overall survival time is 14.5 months for the rare blastoid variant as compared to 53 months for patients with more common forms of MCL such as those composed of homogeneous population of small- to medium-sized cells, confirming the very poor prognosis of the blastoid variant. 9 Our patient cytological examination showed atypical lymphoid cells consistent with blastoid variant with medium to slightly large sized cells and frequently increased nucleocytoplasmic ratios.…”
mentioning
confidence: 88%
“…The blastoid and pleomorphic variants behave more aggressively than other MCL variants. 8 Median overall survival time is 14.5 months for the rare blastoid variant as compared to 53 months for patients with more common forms of MCL such as those composed of homogeneous population of small- to medium-sized cells, confirming the very poor prognosis of the blastoid variant. 9 Our patient cytological examination showed atypical lymphoid cells consistent with blastoid variant with medium to slightly large sized cells and frequently increased nucleocytoplasmic ratios.…”
mentioning
confidence: 88%
“…1 It is an aggressive disease that occurs primarily in older men aged 35 to 80 years, with a median age of 65 years. 1 In patients without a history or a prior diagnosis of systemic lymphomas, primary orbital non-Hodgkin lymphoma arising in the conjunctiva, lacrimal system, eyelids, soft orbital tissue, and extraocular muscles account for 1 to 2% incidence rate. 2 No known risk factors for mantle cell lymphoma have been identified.…”
Section: Epidemiologymentioning
confidence: 99%
“…1 Ocular adnexal lymphoma (OAL) is seen in the fifth to seventh decades of life with a slight female predominance. Most (84%) OALs are of low-grade histology; only 16% are of high-grade histology.…”
Section: Introductionmentioning
confidence: 99%
“…3 Less common B cell lymphoma subtypes include follicular lymphoma (FL), diffuse large B cell lymphoma (DLBCL), plasmacytoma, lymphoplasmacytic lymphoma, mantle cell lymphoma (MCL), and even hairy cell leukemia. 1,4,5 Because of distinctive epidemiologic patterns in different geographic areas as well as different environmental and genetic factors, several microbiologic agents, especially Chlamydophila psittaci, have been considered to play a role in the etiology of OAL. [6][7][8] In 2004, Ferreri et al 9 reported that C psittaci DNA was detected with targeted polymerase chain reaction in 80% of patients with ocular adnexal extranodal marginal zone B cell lymphoma.…”
Section: Introductionmentioning
confidence: 99%